KAJIAN KUALITAS AIR DAERAH IRIGASI SEKAMPUNG BATANGHARI (Studi Kasus Pada Blok Tersier KBH1. Ki) - , Asnal Diansyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chemical fertilizer which used by farmers and the effect of rain which contain of nitrogen in the rice field plots KBH1. Ki area of 13 hectares can contribute to pollution in the drainage channel. Surface runoff pollution from rice fields containing amonia, nitrite, nitrate, phosphate and calium. The study was conducted to determine the contribution of chemical fertilizer on water quality in the drainage channel after the rain. The method used to measurement of water discharge and water sampling in the irrigation channel and drainage channel. Pollution Index based on analysis performed in order to obtain the value of the water quality status of water quality and agricultural pollution load. Water balance analysis was conducted to determine the changes that occur in the inundation of rice fields and the balance of nutrients due to runoff first period on December 10, 2013, second period on December 25, 2013 and third period on January 9, 2014. Concentration and pollution load parameters pH , ammonia, nitrite, nitrat, phosphate and calium high enough corresponding period ( of time ) are reviewed. The results of the analysis of pollution index in the drainage channel showed mild polluted water conditions, especially in the first period. Due to the occurrence of rainfall and surface runoff obtained from the puddle of water level changes daily at 6.51 mm in the first period, 6.78 mm in the second period and 7,13 mm in the third period. Urea fertilizier soluble in the drainage channel as much as 3.395 % of total input Urea (water of irrigation + rain water + fertilizer ) as much as 146.883 kg which occurred during a third period for 2 hours. TSP fertilizier pollution largest 0.357 % that occurred in third period for 2 hours of total input TSP (water of irrigation + fertilizer) of 195.717 kg, while SP36 fertilizier pollution as much as 0.342 % of the total input SP36 (water of irrigation + fertilizer) as many as 260.916 kg happened for 2 hours in third period. KCL fertilizer pollution as much as 3.757 % of the total input KCL (water of irrigation + fertilizer) of 188.573 kg which occurred during a third period for 2 hours. Keywords: fertilizer, drainage channel, index of pollution, agricultural pollution load